The Efficacy of Gabapentin in the Treatment of Alcohol Use Disorder - Radosław Zaucha; Magdalena Gajkiewicz; Małgorzata Zając; Julia Silldorff; Tomasz Fura; Marcin Dudek; Zuzanna Felińska; Oliwia Iszczuk; Stanisław Anczyk; Magdalena Jaskółka (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Alcohol Use Disorder (AUD) is a significant medical condition characterized by an inability to control alcohol use despite adverse consequences, ranging from occasional excessive drinking to daily dependency. Treatment for AUD involves a combination of pharmacological and behavioral approaches. Common medications include Disulfiram, Naltrexone, and Acamprosate, with newer therapies like gabapentin providing additional options. This review aims to systematically evaluate and synthesize available research concerning the use of gabapentin in the treatment of AUD. Methods: This review was created based on 4 articles found in PubMed and Pubmed database based on keywords: "alcohol use disorder", "gabapentine in alcohol use disorder" and "gabapentine". State of knowledge: Gabapentin was originally developed for its anticonvulsant properties and tts primary use was to treat epilepsy by reducing the frequency of seizures in patients with refractory epilepsy. Gabapentin's effectiveness in treating Alcohol Use Disorder is founded on its ability to modulate neuronal excitability. Recent RCTs have demonstrated the efficacy of gabapentin in alcohol use disorder, especially for patients with a history of significant alcohol withdrawal symptoms, though the extended-release formulation of gabapentin proved ineffective. Conculsions: The overall findings suggest gabapentin holds promise as a treatment for AUD, particularly in individuals with significant withdrawal symptoms, but additional studies are required to fully establish its efficacy and optimal use.